2009
DOI: 10.1038/ajg.2009.78
|View full text |Cite
|
Sign up to set email alerts
|

Urgent vs. Non-Urgent Endoscopy in Stable Acute Variceal Bleeding

Abstract: For patients who present with hemodynamically stable variceal bleeding, hemostasis after endoscopy is high, and the time to endoscopy does not appear to be associated with mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
2
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(65 citation statements)
references
References 17 publications
0
57
2
3
Order By: Relevance
“…3,4 In a retrospective study of patients who came with acute variceal bleeding but were hemodynamically stable, there was no significant difference in mortality in patients with endoscopy performed within 4 hours versus 8 hours or 12 hours. 5 In contrast, another study which found delayed endoscopy (endoscopy time > 15 hours) as a risk factor for increase mortality in acute variceal bleeding. 6 It is our opinion that the urgency is dictated by the severity of bleeding and the clinical setting.…”
Section: Endoscopic Diagnosis Of Variceal Hemorrhagementioning
confidence: 97%
“…3,4 In a retrospective study of patients who came with acute variceal bleeding but were hemodynamically stable, there was no significant difference in mortality in patients with endoscopy performed within 4 hours versus 8 hours or 12 hours. 5 In contrast, another study which found delayed endoscopy (endoscopy time > 15 hours) as a risk factor for increase mortality in acute variceal bleeding. 6 It is our opinion that the urgency is dictated by the severity of bleeding and the clinical setting.…”
Section: Endoscopic Diagnosis Of Variceal Hemorrhagementioning
confidence: 97%
“…This is even more vital in patients admitted with hematemesis in whom the importance of early endoscopy is paramount. 22 Indeed, risk factors for inhospital mortality in patients with AVB not only include delayed endoscopy but also failure of first endoscopy, hematemesis, and severity of cirrhosis. If the application of hemostatic powder, through its simplicity, could reduce the proportion of delayed endoscopies, it would compare favorably with the best series reported to date 23 in terms of immediate hemostasis and failure to control bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…Second, because the sample size of our two cohorts can be considered as limited. However, it is in the range of previous published series where the number of patients included per year is compared [9,27,30]; furthermore, the substantial number of events (rebleeding and death) at six months allowed us to investigate through multivariate analysis the therapeutic changes observed during this last decade that significantly impact on survival. Finally, the non-use of early TIPS in our second period allows us to better evaluate the importance of the appropriate use of medical resources, available anywhere, to treat VB.…”
Section: Discussionmentioning
confidence: 99%